2016
DOI: 10.1002/lom3.10107
|View full text |Cite
|
Sign up to set email alerts
|

Accurate oxygen measurements on modified Argo floats using in situ air calibrations

Abstract: Oxygen is an important tracer for biological processes in the ocean. Measuring changes in oxygen over annual cycles provides information about photosynthesis and respiration and their impact on the carbon cycle. Long-term, accurate oxygen measurements over wide areas are needed to determine changes in ocean oxygen content and oxygen deficient zones. Oxygen sensors have been increasingly mounted on Argo floats that profile between 2000 m and the surface. Most of these measurements are currently too inaccurate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 37 publications
7
91
0
Order By: Relevance
“…Johnson et al (2015) obtained both significant positive and negative drift for a fleet of 29 floats with a range of −0.9 to +1.3 % year −1 and an insignificant mean of +0.2 % year −1 , from which they concluded that optodes are stable in-situ on average. Finally, Bushinsky et al (2016) reported a significant optode drift for 10-12 out of 14 optodes with both positive and negative drift and a significant mean trend of −0.12 % year −1 .…”
Section: From Argo-o 2 Float-mounted Optodesmentioning
confidence: 91%
See 2 more Smart Citations
“…Johnson et al (2015) obtained both significant positive and negative drift for a fleet of 29 floats with a range of −0.9 to +1.3 % year −1 and an insignificant mean of +0.2 % year −1 , from which they concluded that optodes are stable in-situ on average. Finally, Bushinsky et al (2016) reported a significant optode drift for 10-12 out of 14 optodes with both positive and negative drift and a significant mean trend of −0.12 % year −1 .…”
Section: From Argo-o 2 Float-mounted Optodesmentioning
confidence: 91%
“…Nicholson and Feen (2017), in fact, confirm a positive zero intercept based on field data. Furthermore, Bushinsky et al (2016), Drucker and Riser (2016), and Nicholson and Feen (2017) show that a slope correction alone might be insufficient at low O 2 levels, while it is appropriate near 100 % O 2 saturation.…”
Section: Drift Charactermentioning
confidence: 99%
See 1 more Smart Citation
“…Precise and accurate measurements of O 2 concentration are currently achieved a variety of ways including with chemical sensors and traditional wet chemistry methods (titrations) (Carpenter, 1965;Johnson et al, 2015;Bushinsky et al, 2016). In recent years, investigators have improved the stability and calibration procedures for O 2 sensors so that they can operate autonomously for long deployments (Bushinsky and Emerson, 2013;Bittig and Körtzinger, 2015;Johnson et al, 2015;Bushinsky et al, 2016).…”
Section: Challenges In the Use Of Gas Tracersmentioning
confidence: 99%
“…In recent years, investigators have improved the stability and calibration procedures for O 2 sensors so that they can operate autonomously for long deployments (Bushinsky and Emerson, 2013;Bittig and Körtzinger, 2015;Johnson et al, 2015;Bushinsky et al, 2016). However, regardless of the precision at which O 2 is measured, it is still necessary to separately quantify the biological and physical fluxes of O 2 in order to calculate the rate of net community O 2 production.…”
Section: Challenges In the Use Of Gas Tracersmentioning
confidence: 99%